Trichosporon spp.: an emerging fungal pathogen - Montoya Mendoza, Alexandra Margarita; González González, Gloria María (UANL. Facultad de Medicina, 2014)
Trichosporon spp. has gained importance as the cases of immunosuppressed patients increase. The genus Trichosporon includes 6 species of clinical relevance that may cause supericial infections, such as white piedra and onychomycosis, or deep and invasive infections with high mortality rates. These microorganisms have a broad geographical distribution and some species are resistant to antifungal drugs in vitro. The present paper is a review on the virulence factors, associated infections, and in vitro susceptibility of the species with the highest incidence as pathogenic agents in humans.